Wings of the wind - Cossette, Connilyn (Cossette, Connilyn. Out from Egypt, 2017)
Cossette Consistently Brings the Old Testament to Life in an Engrossing, Fresh New Way Alanah, a Canaanite, is no stranger to fighting and survival. When her family is killed in battle with the Hebrews, she disguises herself and sneaks onto the battlefield to avenge her family. The one thing she never counted on was surviving. Tobiah, a Hebrew warrior, is shocked to find an unconscious, wounded woman among the Canaanite casualties. Compelled to bring her to a Hebrew healer back at their camp, he is soon confronted with a truth he can't ignore: the only way to protect this enemy is to marry her. Unused to being weak and vulnerable, Alanah submits to the marriage--for now. As she comes to know and respect Tobiah and his people, however, she begins to second-guess her plans of escape. But when her past has painfully unanticipated consequences, the tentative peace she's found with Tobiah, the Hebrews, and Yahweh is shaken to the core. Can Alanah's fierce heart and strength withstand the ensuing threats to her life and all she's come to love?